Productivity costs of lifelong smoking—the Northern Finland Birth Cohort 1966 study - Rissanen, Ina; Nerg, Iiro; Oura, Petteri; Huikari, Sanna; Korhonen, Marko (European journal of public health, 2024)
Background Smoking is one of the leading causes of impaired health and mortality. Loss of paid and unpaid work and replacements due to morbidity and mortality result in productivity costs. Our aim was to investigate the productivity costs of lifelong smoking trajectories and cumulative exposure using advanced human capital method (HCM) and friction cost method (FCM). Methods Within the Northern Finland Birth Cohort 1966 (NFBC1966), 10 650 persons were followed from antenatal period to age 55 years. The life course of smoking behaviour was assessed with trajectory modelling and cumulative exposure with pack-years. Productivity costs were estimated with advanced HCM and FCM models by using detailed, national register-based data on care, disability, mortality, education, taxation, occupation and labour market. A two-part regression model was used to predict productivity costs associated with lifelong smoking and cumulative exposure. Results Of the six distinct smoking trajectories, lifetime smokers had the highest productivity costs followed by late starters, late adult quitters, young adult quitters and youth smokers. Never-smokers had the lowest productivity costs. The higher the number of pack-years, the higher the productivity costs. Uniform patterns were found in both men and women and when estimated with HCM and FCM. The findings were independent of other health behaviours. Conclusions Cumulative exposure to smoking is more crucial to productivity costs than starting or ending age of smoking. This suggests that the harmful effects of smoking depend on dose and duration of smoking and are irrespective of age when smoking occurred.